The Effect of Work Flexibility and Work Environment on Job Satisfaction through Work–Life Balance among PLN Pinrang Employees - Ikram Saprillah Natsir; Kasnaeny Karim; Baharuddin Latief (Jurnal Ilmu Manajemen Profitability, 2026)
Despite growing attention to work flexibility and work environment in human resource management literature, limited studies have simultaneously examined their direct and indirect effects on job satisfaction through work–life balance within public utility organizations. This study aimed to analyze the influence of work flexibility and work environment on job satisfaction, with work–life balance acting as a mediating variable among employees of PLN UP3 Pinrang–ULP Lakawan. The research employed a quantitative design using primary data collected through structured questionnaires distributed to all 64 employees using a census sampling technique. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 to evaluate both the measurement and structural models. The results indicated that work flexibility had a positive and significant effect on work–life balance and job satisfaction. Similarly, the work environment significantly influenced both work–life balance and job satisfaction. Furthermore, work–life balance showed a positive and significant effect on job satisfaction and partially mediated the relationships between work flexibility and job satisfaction as well as between work environment and job satisfaction. The model demonstrated strong explanatory power, with the structural model explaining a substantial proportion of variance in both work–life balance and job satisfaction. These findings highlight the importance of implementing flexible work arrangements and creating a supportive work environment to improve employees’ work–life balance and ultimately enhance job satisfaction. The study contributes to human resource management literature by providing empirical evidence from a public utility organizational context and offers practical implications for organizations seeking to improve employee well-being and organizational performance.